2011
DOI: 10.1007/s11606-011-1770-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Spirometry Use and Accuracy of COPD Diagnosis in Primary Care

Abstract: BACKGROUND: It is unclear if primary care physicians are following guidelines or using other patient characteristics and factors to determine when to perform spirometry in patients at risk for COPD. It is also unclear to what degree a diagnosis of COPD is accurately reflected by spirometry results. OBJECTIVES: To examine characteristics associated with use of spirometry in primary care for patients with increased risk for COPD and to determine the accuracy of COPD diagnosis in patients with spirometry. DESIGN:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
(30 reference statements)
0
31
0
2
Order By: Relevance
“…21 Many providers rely on symptoms to diagnose COPD, even though multiple studies have shown that diagnosis based on symptoms and physical examination is unreliable. 7,[22][23][24] Previous studies have highlighted that only approximately one-third of patients given a new diagnosis of COPD undergo spirometry to verify the diagnosis. 2,6 Studies in primary care physicians suggest that many providers believe that spirometry is not neces sary to diagnose COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Many providers rely on symptoms to diagnose COPD, even though multiple studies have shown that diagnosis based on symptoms and physical examination is unreliable. 7,[22][23][24] Previous studies have highlighted that only approximately one-third of patients given a new diagnosis of COPD undergo spirometry to verify the diagnosis. 2,6 Studies in primary care physicians suggest that many providers believe that spirometry is not neces sary to diagnose COPD.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Th is gap between National Quality Forum recommendations and practice is likely driven by attitudes and beliefs about the lack of clinical utility of spirometry in the management of patients with COPD. [7][8][9][10] Empirical…”
mentioning
confidence: 99%
“…1 COPD has been estimated to occur in up to 25% of the population aged 40 years and older [1][2][3] ; however, both overdiagnosis and underdiagnosis pose challenges in daily practice, resulting in inappropriate patient management. [2][3][4][5][6][7][8][9][10] COPD guidelines recommend the use of a low ratio of forced expiratory volume in 1 second to forced vital capacity (FEV 1 /FVC) to establish the diagnosis in patients with chronic respiratory symptoms or those at risk. 1,11,12 There is currently no consensus on the best criteria to be used for the spirometric confirmation of a clinical diagnosis of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…1,[11][12][13][14][15][16][17] Prevalence studies have shown discordance between the fixed ratio and LLN, suggesting potential overdiagnosis by the former or underdiagnosis by the latter. 3,4,8,18,19 This controversy persists because of the absence of a reference standard for the diagnosis of COPD. 19 The associations of the 2 criteria with clinical outcomes have been assessed in a few studies, with unclear results on the relative superiority of 1 criterion over the other when it comes to their relationship with different clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Benzer çalışmalarda da, bireylerin BKİ değerleri ile KOAH tanısı almış olma durumları arasında istatistiksel açıdan anlamlı bir ilişki bulunamamıştır. 21 Çalışmamızda, Nevşehir il merkezinde yaşa-yan 40 yaş ve üzeri nüfusta, KHH görülme sıklığı (FEV 1 /FVC<%70) %12,1 olarak tespit edilmiştir (Tablo 4). Liu ve ark.…”
Section: Bulgularunclassified